COVID-19: Turning a Pandemic into a Learning Opportunity for Senior Medical Students - John C. Garman (University Library System, University of Pittsburgh, 2020)
Normally, the 4th year of medical school in the United States is when students narrow down their clinical experiences to reflect their interests, and prepare for applying to residency programs. The COVID-19 pandemic has made this process difficult, forcing many senior students from the frontlines to the sidelines. Policy changes have forbidden students from attending some in-person rotations and participating in operational procedures. The impact that COVID-19 has had on medical curricula varies between institutions, with many being hindered significantly by the event. However, my institution is using novel approaches to patient care, allowing senior students to help. Senior students are using telecommunication to connect with patients and assist them with their medical questions and needs. They are acting as Transitional Care Providers and Patient Navigation Assistants, allowing them to use their knowledge and skills to help both the patients and the healthcare system. Other students are acting as "COVID-19 case-trackers," attempting to mitigate the spread of infections. By allowing students to take on these roles during the pandemic, institutions like mine are making this time one of valuable experience and learning. For some senior medical students, the COVID-19 pandemic, with all of its hardships, has become an invaluable learning opportunity and a chance to serve their community.